"Mulukī Ain" of 1854 Nepal's First Legal Code - Khatiwoda, Rajan (Documenta Nepalica, 2021)
The Mulukī Ain of 1854-the law code with constitutional features drafted at the initiative of Prime Minister Jaṅga Bahādura Rāṇā-is the foundational legal text for modern Nepal. It covers almost every aspect of public, criminal, private and religious law, ranging from the organisation of the state and courts to murder and other delicts, the workings of the caste system and the joint family, matters of purity and penance, customary law, widow-burning and witchcraft. As such, the Mulukī Ain is a unique source not only for the political, social and economic life of 19th-century Nepal, but also for the place of traditional Hindu jurisprudence in South Asian legal cultures.